Strengthening School Management: Administrative and Supervisory Practices in Southern Pinukpuk District Public Elementary Schools - Bascos, Chariethel; Sabado, Adriano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study analyzed the administrative and supervisory practices of public elementary school heads in Southern Pinukpuk District, Kalinga, for School Year 2025-2026. It determined the profile of the respondents, their level of proficiency in administrative and supervisory functions, the problems they encountered, and the significant differences in their perceptions when grouped according to position. The study used a descriptive-survey design with total enumeration of 20 school heads composed of 14 principals and 6 head teachers. Data were gathered through a structured questionnaire, unstructured interviews, and documentary analysis, and were analyzed using frequency count, percentage, weighted mean, and t-test. Findings showed that school heads were very proficient in most administrative functions, particularly planning, organizing, school operations, fiscal management, communication, and community relations. Available supervisory data also showed very proficient ratings in in-service training, pupil development, staff development, and classroom evaluation, while research was rated proficient. Problems were generally slightly serious to moderately serious, with significant differences in physical plant facilities, decision-making, communication, research, and curriculum enhancement. The study concludes that school heads in Southern Pinukpuk District demonstrate strong leadership capacity, yet continued support is needed in facilities improvement, research use, data management, communication, and curriculum work.
Keywords: Administrative Practices; Instructional Leadership; School Heads; School Management; Supervisory Practices.